Comparative study of porting complications by implantation under and on the pectoral muscle in cancer patients at Shahid Beheshti and Hazrat Masoumeh hospitals during the years 2010-2014 - Amrollah Salimi; Faeghe Mollaabassi; Sajjad Rezvan; Enayatollah Noori; Amirhossein Naderi; Nargess Kalhor; Sara Afshari (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2020)
Introduction: Porting is one of the invasive processes that is usually associated with significant complications in patients. Therefore, this study was conducted to compare the effects of porting in two ways: implanted under the muscle and on the pectoralis muscle of cancer patients. Materials and Methods: In this retrospective cohort study, a comparison was made between patients whose ports were implanted under the muscle and patients whose ports were implanted on the pectoralis muscle. The level of significance was considered to be 0.05. Results: The mean age of the patients was 17.83±19.1 months. 51.2% (42 patients) were boys and 48.8% (40 patients) were girls. Comparison of the average success (percentage) of the ports (P = 0.419), the incidence of infection (P = 0.241), the incidence of skin necrosis (P = 0.077) and the rate of displacement (P = 0.005). P) In patients between the two groups, there was no significant statistical difference in terms of port location. Conclusion: The present study showed that there was no statistically significant difference in the amount of successful porting and comparison of infection, skin necrosis and port displacement in the studied patients, despite the higher incidence of porting group effects on the pectoralis muscle compared to the sub muscular.